Judicial Discretion and Joint Property Interpretation at Banten PTA: Analyzing Justice, Contribution, and Legal Adaptation - Karmawan karmawan; Oneng Nurul Bariyah; Yahaya Niwae; Hendra Pertaminawati (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2025)
This study aims to analyze the role of judicial discretion in interpreting the division of joint property (gono-gini) in the Banten High Religious Court (PTA), with a focus on factors of fairness and contribution. Formal norms such as Article 97 of the Compilation of Islamic Law (KHI), which stipulates a 50:50 division, are often inadequate when faced with unequal economic and non-economic contributions, bad faith, and the socio-economic vulnerability of the weaker party. This study uses a content analysis method on appeal decisions from 2021-2025, supplemented by a review of Islamic law literature and Maqasid al-shari'ah. The results of the study indicate that judges use discretion to adjust the distribution proportion based on actual contributions, the child's best interests, and the principle of benefit. The maqāṣid al-sharī‘ah framework serves as a normative basis that binds deviations to remain proportional and oriented towards substantive justice. The findings also emphasize the need for interpretive guidelines, gender-friendly evidentiary standards, and strengthening mediation and prenuptial education to reduce disparities in decisions. This study concludes that judicial discretion is not merely a technical freedom, but a teleological instrument for realizing adaptive and inclusive justice in the Indonesian religious court system.